Relationship of PIEZO1 and PIEZO2 vascular expression with diabetic neuropathy - Garcia-Mesa, Yolanda; Cabo, Roberto; González-Gay, Mario; García-Piqueras, Jorge; Viña, Eliseo; Martínez, Irene; Cobo, Teresa; García-Suárez, Olivia (Frontiers in Physiology, 2023)
Introduction: Diabetic distal symmetric polyneuropathy (DDSP) is the most prevalent form of diabetic neuropathy (DPN), and 25% of patients develop pain in their toes. DDSP is associated with increased cutaneous microvessel density (MVD), reduced skin blood flow, endothelial dysfunction, and impaired fluid filtration with vasodilation. The Piezo family of mechanosensitive channels is known to be involved in the control of vascular caliber by converting mechanical force into intracellular signals. Furthermore, Piezo2 is particularly involved in peripheral pain mechanisms of DDSP patients. To date, very little is known about the number, structure, and PIEZO expression in cutaneous blood vessels (BVs) of individuals with DDSP, and their relation with pain and time span of diabetes.Methods and results: We studied microvessels using endothelial markers (CD34 and CD31) and smooth cells marker (α-SMA) by indirect immunohistochemical assay in sections of the glabrous skin of the toes from patients and controls. Microvessel density was assessed through CD34 and CD31 immunoreaction. MVD determined by CD34 is higher in short-term DDSP patients (less than 15 years of evolution), regardless of pain. However, long-term DDSP patients only had increased blood vessel This is a provisional file, not the final typeset article density in the painful group for CD31. Blood vessels of patients with DDSP showed structural disorganization and loss of shape. The blood vessels affected by painful DDSP underwent the most dramatic structural changes, showing rupture, leakage and abundance of material that occluded blood vessel lumen. Moreover, blood vessels of DDSP patients displayed a Piezo1 slight immunoreaction whereas painful DDSP patients showed an increase of Piezo2 immunoreaction.Discussion: These results suggest that alterations in number, structure, and immunohistochemical profile of specific blood vessels can explain the vascular impairment associated with painful DDSP, as well as the temporal span of diabetes. Finally, this study point out a possible correlation between increased vascular Piezo2 immunostaining and pain, and decreased vascular Piezo1 immunostaining and development vasodilation deficiency.